A High Prevalence Of Vitamin D Deficiency In Children With Steroid Sensitive Nephrotic Syndrome - Zubair, Aasia; Moorani, Khemchand N (Pakistan Journal of Kidney Diseases, 2021)
Vitamin -D deficiency (VDD) is very high in developing countries including Pakistan. It is vital to study vitamin D levels in these children for future interventions. Methods This cross- sectional study on 70 children with SSNS, conducted at National Institute of Child Health (NICH), Karachi from December 2014 - July 2015. Children aged 4-15 years, with SSNS, and more than two relapses and in remission state were included. Serum VD was categorised as sufficiency (>30 ng/ml), insufficiency (< 30), deficiency (<20) and severe deficiency (< 10 ng/ml). Demographics like age, gender, weight, height, body mass index (BMI), disease duration, VD level and outcome was collected and analysed on SPSS 20 using descriptive statistics. RESULTS Among 70 children studied, mean age was 9.69 ±3.31 years and 60% were below 10 years. There was a male preponderance (67%). Mean weight, height and BMI was 28.24 ±9.76 Kg ,122.82 ±16.76 cm and 18.27 ±3.89 Kg/m2 respectively. Mean duration of disease was 5.73 ±3.13 years. Mean VD level was 13.27+7.11 ng/ml. There was suboptimal VD status in 95.71% of cases and it was severe VDD in 37%. Conclusion Our findings of suboptimal VD status in 95.71% of children with SSNS are consistent with VD status in children with various disorders other than SSNS. Majority of children were either VD deficient (51.4%) or severely deficient (37.1%). Further prospective studies on large scale are needed to assess the VD deficiency, its relationship with steroid use and response to VD supplement in children with SSNS.